2020
DOI: 10.1186/s12967-020-02518-2
|View full text |Cite
|
Sign up to set email alerts
|

Cannabis, a cause for anxiety? A critical appraisal of the anxiogenic and anxiolytic properties

Abstract: Background Cannabis has been documented for use in alleviating anxiety. However, certain research has also shown that it can produce feelings of anxiety, panic, paranoia and psychosis. In humans, Δ9-tetrahydrocannabinol (THC) has been associated with an anxiogenic response, while anxiolytic activity has been attributed mainly to cannabidiol (CBD). In animal studies, the effects of THC are highly dose-dependent, and biphasic effects of cannabinoids on anxiety-related responses have been extensiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
56
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(60 citation statements)
references
References 94 publications
(199 reference statements)
3
56
1
Order By: Relevance
“…The majority of cannabis users taking ADHD medication reported that cannabis is beneficial for managing many of the side effects associated with ADHD medication, including stomach ache, headache, loss of appetite, sleeping problems, rebound, moodiness/irritability, and anxiety. While these findings are entirely novel, these self-reports are consistent with previous research demonstrating that acute cannabis use diminishes headache severity (Cuttler et al, 2020), improves appetite (Bonn-Miller et al, 2014), insomnia and sleep related problems (Choi et al, 2020; Cranford et al, 2017; Doremus et al, 2019), irritability (LaFrance et al, 2020), and anxiety (Cuttler et al, 2018; Sharpe et al, 2020) in the broader population. These symptoms represent many of the undesirable side effects that stimulant medications are known to cause and that can contribute to low adherence rates (Berman et al, 2009; Man et al, 2017; Zetterqvist et al, 2013).…”
Section: Discussionsupporting
confidence: 87%
“…The majority of cannabis users taking ADHD medication reported that cannabis is beneficial for managing many of the side effects associated with ADHD medication, including stomach ache, headache, loss of appetite, sleeping problems, rebound, moodiness/irritability, and anxiety. While these findings are entirely novel, these self-reports are consistent with previous research demonstrating that acute cannabis use diminishes headache severity (Cuttler et al, 2020), improves appetite (Bonn-Miller et al, 2014), insomnia and sleep related problems (Choi et al, 2020; Cranford et al, 2017; Doremus et al, 2019), irritability (LaFrance et al, 2020), and anxiety (Cuttler et al, 2018; Sharpe et al, 2020) in the broader population. These symptoms represent many of the undesirable side effects that stimulant medications are known to cause and that can contribute to low adherence rates (Berman et al, 2009; Man et al, 2017; Zetterqvist et al, 2013).…”
Section: Discussionsupporting
confidence: 87%
“…In contrast, individuals in the THC-dominant concentrate group did not report significant changes in anxiety or tension immediately post-use, but a significant reduction in anxiety from baseline did emerge at one-hour post-use. This is notable as human studies generally show an anxiogenic acute effect of THC, especially in high concentrations 50 .…”
Section: Discussionmentioning
confidence: 96%
“…However, some subjective data do show a preference for THC or whole cannabis products in the context of self-medicating for affect issues, with few reports of undesirable effects 50 , 51 . Furthermore, anxiogenic effects induced by more typically seen in individuals who fall into the category of infrequent or non-users, rather than those who use cannabis or THC products on a more regular basis 25 , 50 . Importantly, anxiety and tension levels were low overall in the study and do not reflect clinical levels of negative affect.…”
Section: Discussionmentioning
confidence: 99%
“…Our finding was consistent with an online survey of medical cannabis users registered with a Canadian licensed producer, which found that anxiety was the most common mental health condition that cannabis was prescribed to treat (Turna et al 2019). This could be a reflection of the anxiolytic properties of cannabinoids, especially the use of CBD, which is suggested as an adjunctive treatment for anxiety or stress-related disorders (Sharpe et al 2020). The possible anxiolytic effects of CBD and other cannabinoids are demonstrated to mediate anxiety, stress, and restlessness in several animal and human studies (Crippa et al 2009;Fraguas-Sánchez & Torres-Suárez, 2018).…”
Section: Discussionmentioning
confidence: 99%